Wages of freedom : fifty years of the Indian nation-state - Chatterjee, Partha 1947- (New Delhi ; New York : Oxford University Press, 1998)
Contributed articles.
Includes bibliographical references.
Keywords: Federal government -- India; India -- Politics and government -- 1947-